Investigating Community Involvement and Public Interests in the Alexandra Renewal Programme (ARP) Implementation and Management - Koenaite, Mokgaetsi (University of the Witwatersrand, Johannesburg, 2023)
The promise of revitalisation and restoration of rural and urban areas came with the advent of democracy in most South African cities in the 1990s. This was accomplished through the implementation of urban renewal programmes that prioritised housing-a critical issue in the country. The Alexandra Renewal Programme (ARP) is used as a case study in the paper. The topic is about investigating a public involvement process, assessing public participation as a governance tool, and analyzing housing delivery decision-making procedures. The purpose to discover more information and find new ways in which we can enhance public engagement in urban renewal programmes to establish sustainable humane settlements. The fundamental concern in the report is that there appears to be a disconnect between how policies, rules, and regulations are developed at the national level and how they are formed at the local level- which is the sphere that interacts with the people. The following methodological approaches are used in the report: structured interviews, participant observation, archival materials, and desktop research. The research concludes that decision making in Alexandra must be intimately tied to spatial dynamics in terms of housing location, density, and material used, and that participatory governance must be practiced to ensure that citizens have a say in decisions that affect them.
A research report submitted in fulfillment of the requirements for the Master of Science in Development Planning, In the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Alexandra Renewal Programme; Public Participation; Housing Location; SDG-11: Sustainable cities and communities